1999
DOI: 10.1016/s1074-7613(00)80089-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lupus-like Autoimmune Diseases by Disruption of the PD-1 Gene Encoding an ITIM Motif-Carrying Immunoreceptor

Abstract: PD-1, a 55 kDa transmembrane protein containing an immunoreceptor tyrosine-based inhibitory motif, is induced in lymphocytes and monocytic cells following activation. Aged C57BL/6(B6)-PD-1(-/-) congenic mice spontaneously developed characteristic lupus-like proliferative arthritis and glomerulonephritis with predominant IgG3 deposition, which were markedly accelerated by introduction of a Fas mutation (lpr). Introduction of a PD-1 null mutation into the 2C-TCR (anti-H-2Ld) transgenic mice of the H-2(b/d) backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
1,653
4
23

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,355 publications
(1,714 citation statements)
references
References 58 publications
(4 reference statements)
34
1,653
4
23
Order By: Relevance
“…46 The PD-1 pathway has a crucial role in peripheral tolerance induction and maintenance as mice with deletion of PD-1 gene developed systemic autoimmunity. 47 Injection of PD-1 neutralizing monoclonal antibody into disease-resistant mice resulted in the majority (67%) of the mice developing EAE whereas none of the IgG controls developed disease. Although we failed to detect any significant changes in proportion of CD4 þ Foxp3 þ T cells, it remains to be determined whether antigen-specific Tregs were generated in this model.…”
Section: Discussionmentioning
confidence: 99%
“…46 The PD-1 pathway has a crucial role in peripheral tolerance induction and maintenance as mice with deletion of PD-1 gene developed systemic autoimmunity. 47 Injection of PD-1 neutralizing monoclonal antibody into disease-resistant mice resulted in the majority (67%) of the mice developing EAE whereas none of the IgG controls developed disease. Although we failed to detect any significant changes in proportion of CD4 þ Foxp3 þ T cells, it remains to be determined whether antigen-specific Tregs were generated in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, B6 mice deficient in Fc␥ receptor IIB (Fc␥RIIB) spontaneously develop circulating antichromatin and anti-dsDNA autoantibodies along with immune complex GN and pulmonary vasculitis, whereas Fc␥RIIB-deficient BALB/c mice do not (56). Moreover, B6 mice deficient in programmed death 1 (PD-1) develop a clinical phenotype highlighted by arthritis and GN (57), whereas BALB/c mice deficient in PD-1 develop no signs of arthritis or GN but do develop a lethal dilated cardiomyopathy (58). Thus, discrete immune disturbances elicit SLE-like features in B6 mice, but the identical immune disturbances do not do so in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo functions of PD-1, PD-L1, and PD-L2 have been of interest because PD-1 -/-mice progressively develop autoimmune diseases [12,13]. Since previous studies have shown that PD-L2 expression may be regulated in some cell types by Th2 cytokines or Th2 cells [21], and because asthma is believed to be a Th2-driven disease [23][24][25][26][27][28][29][30][31][32], it was of interest to examine whether PD-L2 can play a role in immune regulation in this context.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 has an immunoreceptor tyrosine-based inhibitory motif in its cytoplasmic domain [9][10][11]. Depending on background strain, PD-1 -/-mice develop increased rates of glomerulonephritis, lupus-like arthritis [12], or autoimmune cardiomyopathy [13]. This provides direct evidence for PD-1 as a negative regulator of immune responses in vivo [13].…”
Section: Introductionmentioning
confidence: 99%